Temporal distribution of sediment yield from catchments covered by different pine plantation areas - Tyas Mutiara Basuki; Irfan Budi Pramono; Rahardyan Nugroho Adi; Esa Bagus Nugrahanto; Diah Auliyani; Wahyu Wisnu Wijaya (Brawijaya University, 2018)
Soil erosion and sedimentation are environmental problems faced by tropical countries. Many researches on soil erosion-sedimentation have been conducted with various results. Quantifying soil erosion-sedimentation and its temporal distribution are important for watershed management. Therefore, a study with the objective to quantify the amount of suspended sediment from catchments under various pine plantation areas was conducted. The research was undertaken during 2010 to 2017 in seven catchments with various percentage of pine coverage in Kebumen Regency, Central Java Province. The rainfall data were collected from two rainfall stations. A tide gauge was installed at the outlet of each catchment to monitor stream water level. The water samples for every stream water level increment were analyzed to obtain sediment concentration. The results showed that monthly suspended sediment of the catchments was high in January to April and October to December, and low in May to September. The annual suspended sediment fluctuated during the study period. Non-linear correlations were observed between suspended sediment and rainfall as well as suspended sediment and percentage pine areas. The line trend between suspended sediment and percentage of pine areas showed that the increase in pine areas decreased suspended sediment, with the slope of the graph is sharp at the percentage of pine areas from 8% to 40%, then is gentle for pine plantation areas more than 40%.